UJI STABILITAS TANAH DI DESA NGELOWETON KECAMATAN MIJEN KABUPATEN DEMAK MENGGUNAKAN METODE AXISYMMETRIC CYLINDER (PLAXIS 2D V20) DENGAN CBR LABORATORIUM (Science and Technology (SciTech), 2022)
Welahan Demak street is a road connecting the cities of Jepara and Demak. Many vehicles pass through this road. Damaged road conditions can endanger passing vehicles. One of the factors of road damage is the weak bearing capacity of the soil. With these problems, it is necessary to know the CBR value through soil stability tests. The soil stability test in this study used the laboratory CBR test method and the Axisymetric Cylinder method (Plaxis 2D V.20). There are 2 samples used in this study, namely soil samples on the right and left of the road. Parameter data needed in soil stability test using Axisymmetric Cylinder method are modulus of elasticity (E), possion ratio (V), internal shear angle, and cohesion (C). The results obtained through the laboratory CBR test were the highest at 3.478%, the lowest at 1.739%. And the results obtained after going through the analysis of the Axisymmetric Cylinder method, the highest CBR value is 3.343% and the lowest is 1.163%.